(untitled) (Global Journal of Human-Social Science, 2025)
The subsidization of fuel means that government pays a fraction of the price residence of Nigeria would have paid when they purchase fuel in the country. Over the years, there has been vehement calls by international organizations like International Monetary Fund (IMF), World Bank (WB), different regimes in the country and even some private individuals on the need to withdraw subsidy on petroleum products in the country. The reason for this position has been anchored on corruption in the subsidy regime and the need for government to reinvest monies saved from subsidy into critical infrastructure in the country. The thrust of this paper was to examine the impact of the withdrawal of subsidy on petroleum products in the country on the wellbeing of residence in Uyo metropolis, Akwa Ibom State, Nigeria. The paper adopted a quantitative method hence information for the paper was sourced through the primary means like interview and Focused Group Discussion (FGD). For cross-validation of field information, journal articles were also reviewed for empirical evidences.